2019
DOI: 10.1021/acs.jpca.9b06331
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Effect of Mineral Dust on Secondary Organic Aerosol Formation by Accretion Reactions of Closed-Shell Organic Compounds

Abstract: The effect of dust aerosols on accretion reactions of water, formaldehyde and formic acid was studied in the conditions of Earth's troposphere using at the DLPNO-CCSD(T)/aug-cc-pVTZ//ωB97X-D/6-31++G** level of theory. Detailed analysis of the reaction mechanisms in the gas phase and on the surface of mineral dust, represented by mono-and tri-silicic acid, revealed that mineral dust has the potential for decreasing reaction barrier heights. Specifically, at 0 K, mineral dust can lower the apparent energy barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 92 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…The development of GO as implemented in ABCluster, has eliminated this obstacle to a large extent, making a series of productive NPF studies possible [32, 96, 167, 172–197] and revealing valuable insights into atmospheric chemistry (see Figure 7 for some examples). ABCluster has been regarded as a standard tool in this field [198–200].…”
Section: Applicationsmentioning
confidence: 99%
“…The development of GO as implemented in ABCluster, has eliminated this obstacle to a large extent, making a series of productive NPF studies possible [32, 96, 167, 172–197] and revealing valuable insights into atmospheric chemistry (see Figure 7 for some examples). ABCluster has been regarded as a standard tool in this field [198–200].…”
Section: Applicationsmentioning
confidence: 99%
“…Many of the simple components of mineral dust by themselves, such as α-Al 2 O 3 , SiO 2 , TiO 2 , α-Fe 2 O 3 , feldspars, carbonates, sulfates, or most importantly NH 3 -deactivated ATD, had observed rate constants smaller by up to 3 orders of magnitude compared to Chinese desert dust (CDD), montmorillonites, or ATD. This fact complicates the investigations but throws us in the right direction compared to the long-held view that the reactivity of mineral dust followed the mixing ratio of its components as in Usher et al This result also puts a question mark on the theoretical approach taken by Keshavarz et al who took ortho -silicic or trisilicic acid as a surrogate for mineral dust materials, which is a truly questionable approach given the conclusions of Kameda et al…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using pyridine adsorption monitored using IR DRIFTS, the authors showed that the nitration reaction was accelerated, especially on clay mineral substrates, which underlines the necessity of providing acidic sites for efficient nitration. Many of the simple components of This fact complicates the investigations but throws us in the right direction compared to the long-held view that the reactivity of mineral dust followed the mixing ratio of its components as in Usher et al 2 This result also puts a question mark on the theoretical approach taken by Keshavarz et al 23 who took ortho-silicic or trisilicic acid as a surrogate for mineral dust materials, which is a truly questionable approach given the conclusions of Kameda et al 41 The important group of main messages resulting from our current work that we have formulated in the next section are for the moment unmatched in that these data fill a critical gap in terms of the variability of coverage, as uncertain it may be in terms of numerical accuracy. This holds both for the uptake and for the initial uptake and desorption kinetics (k a , k 0 , and γ 0 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations